Implementasi Pendidikan Agama Islam Dalam Penanaman Budaya Religius Untuk Meningkatkan Pembentukan Karakteristik Islami - Dwi Cahyani, Nabila; Luthfiyah, Rara; Apriliyanti, Vanny; Munawir, Munawir (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Everyone seems concerned about the moral crisis the nation is experiencing. In fact, this behavior is very contrary to the religious traditions and character of the Indonesian nation. Moral degradation will spread to all levels of society if this disaster is allowed to drag on for a long time, what's more considered as normal. Therefore, character education is a priority in various countries in an effort to develop a good generation that will benefit individuals and society overall. This research aims to find out whether PAI learning in the classroom is possible to help students develop strong religious values. The technique used is type library research. The results of the research show that students' religious character can be formed through PAI learning. This is because PAI teachers at these schools are very creative and create a learning plan using various appropriate learning strategies. Thus, PAI education can help students develop their religious character.